ASSISTANCE IN PREPARING FINANCIAL REPORTS USING THE SIAPIK APPLICATION BY INTEGRATING THE TEACHINGS OF TRI N (NITENI, NIROKKE, NAMBAHI) - Chandra Putry, Nur Anita; Putri, Fuadhillah Kirana; Pratama, Yhoga Heru; Fauzi, Fitriya (EMPOWERING HUMANITY, 2024)
This community service focuses on assisting the preparation of financial reports using the Financial Information Recording Application System (SIAPIK) by integrating the Tri N Teachings (Niteni, Nirokke, Nambahi) at the Jogja Car AC Specialist workshop. The workshop, which has been operating for 3 years, has experienced obstacles in financial reporting such as financial records that are still manual and there is still a lack of synchronization between records and actual transactions. This Abdimas will use lecture, discussion, self-assignment, role play, and evaluation methods as problem solving efforts. The service team will provide material in the form of how to make financial reports by integrating the Tri N Teachings (Niteni, Nirokke, Nambahi). The hope is that after participating in this service activity, business actors can recognize and remember how to prepare financial reports in accordance with Indonesian SAK for Micro, Small and Medium Entities (SAK EMKM), imitate and apply the knowledge gained, and develop the preparation of financial reports manually and switch to the SIAPIK accounting application system.